مستوى الاحتراق النفسي لدى الطالب الجامعي دراسة ميدانية بجامعة عمار ثليجي - هالة بن لحبيب; راضية بن بوزيد; عبد الكريم ملياني (My University, 2018)
The study aimed to identify the level of psychological burnout among university students at Ammar Thaliji University in Laghouat, taking into account the following variables: Gender (male - female) Specialization (Psychology - Education Sciences) and the effect of these variables on psychological combustion. The descriptive approach was used in the collection of data and the psychological combustion scale was designed for this purpose. It was applied to a sample of students of psychology and education sciences in the Faculty of Social Sciences consisting of (100) students randomly selected and through statistical processing of data using statistical methods. Frequency, percentages, arithmetic averages, and "T" tests for differences. The study, after processing the statistical package for social sciences (SPSS 20), found the following results ; 1. The level of psychological combustion of the university student at Ammar Thaliji University in Laghouat is weak. 2. There are no statistically significant differences in the level of psychological combustion among university students according to the gender variable (male - female). 3. There are no statistically significant differences in the level of psychological combustion between the averages of university students according to the variable of specialization (psychology - sciences of education). Psychological combustion - university student